Microfluidics size fractionation of paclitaxel-loaded microspheres for breast cancer treatment - Tan, Kah Kee (2016)
Drug-loaded microspheres are widely used in cancer treatment through targeted and sustained drug delivery. In this study, poly(lactic-co-glycolic acid) (PLGA) microspheres loaded with paclitaxel (PTX) are synthesized and size-fractionated using a novel inertial microfluidics strategy (Dean Flow Fractionation) for enhanced inhibition of breast cancer cell proliferation. The polydimethylsiloxane (PDMS) microdevice was characterized by optical imaging methods (high speed and fluorescence) and flow cytometry using fluorescent microbeads. After device optimization, PTX-loaded microparticles were fractionated into 3 different size groups (>5µm, 3-5µm and <3µm) and co-incubated with MCF-7 breast cancer cells. CCK Proliferation (CCK) assay and imaging showed that smaller microparticles (<3µm) were more effective at inhibiting cell proliferation. The developed technology provides a novel high throughput sample preparation method for nanoparticle synthesis and drug delivery systems.